1993
DOI: 10.1677/jme.0.0110325
|View full text |Cite
|
Sign up to set email alerts
|

Direct effect of adenosine on prolactin secretion at the level of the single rat lactotroph: involvement of pertussis toxin-sensitive and -insensitive transducing mechanisms

Abstract: We studied the effect of adenosine on prolactin secretion by the anterior pituitary, and the transduction mechanisms whereby the purine exerts its action. Adenosine inhibited prolactin release in basal and in vasoactive intestinal peptide (VIP)- or TRH-stimulated conditions. Pertussis toxin pretreatment reduced the inhibition of VIP-stimulated prolactin secretion which was induced by adenosine, while it completely abolished the effect of the purine on TRH-evoked prolactin release. In membrane preparations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…(2)). This indicated the presence of A2 receptors and subsequent studies also showed the existence of A1 receptors that are coupled to adenylate cyclase and phospholipase C in several pituitary cell lines [105][106][107][108][109]. More detailed experiments using several complementary methods showed that adenosine receptors are differentially expressed in the different cell types within the anterior pituitary gland [110][111][112].…”
Section: Anterior Pituitary Glandmentioning
confidence: 81%
“…(2)). This indicated the presence of A2 receptors and subsequent studies also showed the existence of A1 receptors that are coupled to adenylate cyclase and phospholipase C in several pituitary cell lines [105][106][107][108][109]. More detailed experiments using several complementary methods showed that adenosine receptors are differentially expressed in the different cell types within the anterior pituitary gland [110][111][112].…”
Section: Anterior Pituitary Glandmentioning
confidence: 81%
“…This negative coupling indicates the involvement of inhibitory G proteins, which are pertussis toxin-sensitive. More recently, Scorziello et al (1993) have demonstrated that the direct effect of adenosine on prolactin secretion in the rat lactotroph involves pertussis toxin-sensitive and -insensitive transducing mechanisms. Adenosine actions have also been studied in cells derived from rat pituitary tumors: GH3 and GH4 cells, which secrete prolactin and growth hormone.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that adenosine inhibits prolactin secretion by acting on a purinergic receptor that modulates the activity of the enzymes adenyl cyclase and phospholipase C by a mechanism depending on membrane G i P activation (16). Other studies have shown that administration of R-PIA inhibits the release of PRL induced by TRH by inhibiting the decrease in phosphatidylinositol and cAMP synthesis in GH 3 cell lines (10).…”
Section: Discussionmentioning
confidence: 99%